Photoinduced Organic Reactions by Employing Pyrene Catalysts - Shiozuka, Akira; Sekine, Kohei; Kuninobu, Yoichiro (Synthesis, 2022)
Pyrene is one of the most attractive polycyclic aromatic hydrocarbons (PAHs) in photochemistry. Based on their redox properties, pyrenes have potential as photosensitizers. In this review, we summarize recent developments in pyrene-catalyzed photoinduced organic reactions occurring via energy transfer or single-electron transfer based on the excited state of the pyrene.1 Introduction2 Photolysis Involving N–O Bond Cleavage or Decarboxylation3 (Cyclo)addition Reactions with Styrenes4 Transformations via Cleavage of C–F, C–I, C–S and C–N Bonds5 Reactions Based on Sensitization-Initiated Electron Transfer (SenI-ET)6 Miscellaneous Transformations7 Conclusion
Keywords: pyrene; photoinduced reactions; organic photosensitizer; electron transfer; organic synthesis